The effect of poly gamma glutamic acid on demineralisation and remineralisation of human dental enamel / Zeeshan Qamar - Zeeshan, Qamar (2017)
It has been suggested that the interaction of glutamic residues in statherin with the hydroxyapatite mineral of human tooth surfaces reduces the kinetics of enamel dissolution during simulated caries challenges. A Japanese traditional foodstuff ‘Natto’ containing poly-γ-glutamic acid (PGGA) may have a similar action. In this study, the efficacy of PGGA in inhibiting demineralisation and promoting remineralisation of human dental enamel under caries-inducing conditions were investigated. Seventy two orthodontically extracted sound premolars (54 for demineralisation study and 18 for remineralisation study, were all varnished, leaving a 2x2 mm2 window on the mid-buccal surfaces), 10.8 g HAp-powder of uniform composition (dental enamel crystallite analogue- 0.2 g/ treatment group for demineralisation study) and 18 HAp pellets of uniform porosity (analogue of dental enamel for remineralisation study) were used in this study. The teeth and the HAp powder were respectively pretreated before being exposed to demineralising solution at various pHs (4.0, 4.5 and 5.0) to induce artificial caries lesions. They were pretreated with PBS (negative control), NaF (0.01%, 0.1% and 0.5% respectively - positive controls) and PGGA (1% and 2%w/v respectively - test groups). The Ca2+ release into the demineralising solution by the teeth and HAp powder (demineralisation study) and the Ca2+ uptake by the teeth and HAp pellets (remineralisation study) were measured using a Ca2+ selective electrode, later used to calculate the rate of calcium loss or gain (RCa2+). Cross sectional microhardness (CSMH) was used to determine the mineral density changes at various depths of induced caries lesions. The results from both these techniques were collated to assess the effect of PGGA in the inhibition of caries lesion formation and mineral recovery. In order to determine the possible mechanism of PGGA in inhibiting demineralisation and promoting remineralisation, the teeth and HAp pellets were treated with PGGA solutions (1% and 2% respectively) and subjected to Fourier Transform Infra-Red (FT- iv IR) analysis. The density of PGGA solutions (1% and 2%) was also measured in order to determine their dynamic viscosities. In this study, it was found that 2% PGGA inhibits the demineralisation of enamel and HAp powder and is more potent compared with the positive controls (0.01% NaF, 0.1% NaF and 0.5% NaF) at the various pHs of demineralising solution (4.0, 4.5 and 5.0). Further 2% (w/v) PGGA was also shown to promote remineralisation of the enamel and HAp pellets at the pH values below the critical pH and was more effective compared with all three concentrations of the positive controls. From the FT-IR analysis, it was shown that PGGA has the capability of coating the enamel and the HAp pellets. The coating ability of PGGA may contribute to the inhibition of dental enamel demineralisation. From the FT-IR analysis, the presence of the COO- group in PGGA may suggest its potential to bind with free Ca2+ present in the solution, remineralising the teeth, as evident by the increasing hardness of enamel from the CSMH study. In this study, it appears that 2% PGGA has a better effect compared with 0.5% NaF in inhibiting enamel demineralisation and promoting remineralisation under caries-inducing conditions.